Thermal Management of a 48 V Lithium-Ion Battery Pack by Semiconductor Refrigeration - Yang, Rui; Li, Kuining; Xie, Yi; Li, Wei; Qian, Yuping; Zhang, Yangjun; Zhang, Hongxiang (Frontiers in Energy Research, 2022)
At present, 48 V mild hybrid battery systems are widely used in hybrid electric vehicles to reduce fuel consumption and emissions. The battery pack often operates at high discharge/charge rates and requires an efficient and compact battery thermal management system (BTMS) to control its temperature, improve its electrical performance and extend its life. Due to their short start-up times and simple structures, semiconductors can provide rapid refrigeration and cool a battery quickly in response to sudden high current rates. Therefore, semiconductors were applied to the BTMS of a 48 V battery. The performance of the semiconductor-based BTMS was studied by simulation and experiment at high discharge rates (up to 9.375 C). Firstly, a thermal model of the BTMS was developed that integrates a resistance-based battery thermal model, a semiconductor thermal model and a three-dimensional fluid-solid coupled heat transfer model. Unlike a traditional thermal model, the proposed model considers the joint influences of SOC, temperature and current on battery resistance and improves the predictive precision of the battery’s thermal behaviour. The thermal model was verified by an experiment, with the results showing that it could precisely describe the temperature increase in the battery (maximum average absolute error within 0.9°C). Finally, the BTMS thermal model was applied to predict the cooling performance of the semiconductor BTMS at an ambient temperature of 37°C and high current rates (up to 9.375 C), which was compared with that of an air-cooled BTMS. The results demonstrate that the semiconductor-based BTMS achieves lower battery temperature than the air-cooled BTMS and ensures a temperature difference within the 48 V pack of <1.6°C.